Identification of the First PAX4-MODY Family Reported in Brazil - Abreu GM; Soares CAPD; Tarantino RM; da Fonseca ACP; de Souza RB; Pereira MFC; Cabello PH; Rodacki M; Zajdenverg L; Zembrzuski VM; Campos Junior M (Diabetes, Metabolic Syndrome and Obesity, 2020)
Gabriella de Medeiros Abreu,1,* Camila de Almeida Pereira Dias Soares,1,* Roberta Magalhães Tarantino,2,3 Ana Carolina Proença da Fonseca,1 Ritiele Bastos de Souza,1 Maria de Fátima Carvalho Pereira,4 Pedro Hernan Cabello,1,5 Melanie Rodacki,2 Lenita Zajdenverg,2 Verônica Marques Zembrzuski,1 Mário Campos Junior1 1Human Genetics Laboratory, Oswaldo Cruz Institute, Oswaldo Cruz Foundation, Rio de Janeiro, Brazil; 2Diabetes and Nutrology Section, Internal Medicine Department, Federal University of Rio de Janeiro, Rio de Janeiro, Brazil; 3Ambulatory of Diabetes, State Institute for Diabetes and Endocrinology Luiz Capriglione, Rio de Janeiro, Brazil; 4Clinical Pathology Department, Federal University of Rio de Janeiro, Rio de Janeiro, Brazil; 5Laboratory of Genetics, School of Health Science, University of Grande Rio, Rio de Janeiro, Brazil*These authors contributed equally to this workCorrespondence: Mário Campos Junior JuniorHuman Genetics Laboratory,Oswaldo Cruz Institute, Oswaldo Cruz Foundation, Pavilhão Leônidas Deane, Sala 615, Avenida Brasil 4365, Rio de Janeiro 21040-360, RJ, BrazilTel +55 21 3865 8192Email mario.junior@ioc.fiocruz.brPurpose: The aim of this study was to sequence the coding region of the PAX4 gene in a Brazilian cohort with clinical manifestations of monogenic diabetes.Patients and Methods: This study included 31 patients with autosomal dominant history of diabetes, age at diagnosis ≤ 40 years, BMI < 30 kg/m2, and no mutations in GCK or HNF1A, HNF4A, and HNF1B. Screening of the PAX4 coding region was performed by Sanger sequencing. In silico algorithms were used to assess the potential impact of amino acid substitutions on protein structure and function. Additionally, PAX4-MODY family members and 158 control subjects without diabetes were analyzed for the identified mutation.Results: The molecular analysis of PAX4 has detected one missense mutation, p.Arg164Gln (c.491G>A), segregating with diabetes in a large Brazilian family. The mutation was absent among the control group. The index case is a woman diagnosed at 32 years of age with polyneuropathy and treated with insulin. She did not present diabetic renal disease or retinopathy. Family members with the PAX4 p.Arg164Gln mutation have a heterogeneous clinical manifestation and treatment response, with age at diagnosis ranging from 24 years to 50 years.Conclusion: To the best of our knowledge, this is the first study to report a PAX4-MODY family in Brazil. The age of PAX4-MODY diagnosis in the Brazilian family seems to be higher than the classical criteria for MODY. Our results reinforce the importance of screening large monogenic diabetes families for the understanding of the clinical manifestations of rare forms of diabetes for the specific and personalized treatment.Keywords: diabetes mellitus, monogenic diabetes, MODY, PAX4, mutation